A new species of Salvia section Membranaceae from Guerrero, México - Fragoso-Martínez, Itzi; Martínez-Gordillo, Martha (Instituto de Ecología, A.C., 2013)
A new species of Salvia section Membranaceae is described and illustrated: Salvia confertispicata belongs to subsection Lophanthoideae and shares morphological similarities with Salvia mocinoi; nevertheless, the former differs in having compact inflorescences, rhombic ascendant bracts with caudate apex and cuneate base, glabrate calyx at anthesis, an invaginated corolla tube which is the longest of all the species in subsection Lophanthoideae. The new species had only been collected in the state of Guerrero, where it is commonly found in oak forests, pine-oak forests, pine forests, cloud forests, and tropical deciduous forests.